2008
DOI: 10.1086/592171
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Viral Clearance, Viral Load, and Genotype Distribution of Hepatitis C Virus (HCV) in HIV‐Infected Patients with Anti‐HCV Antibodies in Europe

Abstract: More than three-quarters of the HIV- and HCV Ab-positive patients in EuroSIDA showed active HCV replication. Viremia was more frequent in IDUs and, conversely, was less common in HBsAg-positive patients. Of the patients with HCV viremia analyzed, 53% were found to carry HCV genotype 1, and this genotype was associated with greater serum HCV RNA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
99
3
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 43 publications
(49 reference statements)
20
99
3
4
Order By: Relevance
“…Close monitoring of RNA levels may therefore help to identify those individuals who are or are not likely to clear HCV without intervention [230]. After acute infection, it has been suggested that progressive liver damage may occur more rapidly than has been historically reported in coinfected individuals [231].…”
Section: Clinical Picture and Natural Historymentioning
confidence: 99%
“…Close monitoring of RNA levels may therefore help to identify those individuals who are or are not likely to clear HCV without intervention [230]. After acute infection, it has been suggested that progressive liver damage may occur more rapidly than has been historically reported in coinfected individuals [231].…”
Section: Clinical Picture and Natural Historymentioning
confidence: 99%
“…Indeed, the incidence and prevalence of HCV genotype 4 are increasing in the Western world, especially among intravenous drug users, 3 and a recent study has shown that 15% of European patients coinfected with human immunodeficiency virus carry HCV genotype 4. 4 Modeling suggests that HCV genotype 4 could play an important role in the future HCV burden in industrialized countries. 5 Further studies are warranted to assess the frequency of undetected HCV RNA with the CAP-CTM assay.…”
mentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Kendal ve ark [21] Güneydo¤u Anadolu bölge-sinde yapt›klar› bir araflt›rmada, anti-HCV pozitif hastalar›n %56's›nda HCV-RNA testini pozitif bulmufllard›r. Bu oran bizim araflt›rmam›zdaki sonuçlara göre daha dü-flük düzeydedir.…”
Section: Tart›flmaunclassified